Defective iron-oxide nanoparticles synthesised by high temperature plasma processing: a magnetic characterisation versus temperature. (26th September 2016) - Balasubramanian, C; Joseph, B; Orpe, PB; Saini, NL; Mukherjee, S; Dziedzic-Kocurek, K; Stanek, J; Di Gioacchino, D; Marcelli, A
Abstract: Magnetic properties and phase compositions of iron-oxide nanoparticles synthesised by a high temperature arc plasma route have been investigated by Mössbauer spectroscopy and high harmonic magnetic AC susceptibility measurements, and correlated with morphological and structural properties for different synthesis conditions. The Mössbauer spectra precisely determined the presence of different iron-oxide fractions in the investigated nanoparticles, while the high harmonic magnetic susceptibility measurements revealed the occurrence of metastable magnetic phases evolving in temperature and time. This study illustrates magnetic properties and dynamics of the magnetic configurations of iron-oxide nanoparticles grown by high temperature plasma, a process less explored so far but extremely useful for synthesising large numbers of nanoparticles for industrial applications.